Risk of venous thromboembolism during and after hospitalisation in patients with inflammatory bowel disease activity - Chu, Thomas P.C.; Grainge, Matthew J.; Card, Timothy R. (Wiley, 2018)
Background: Inflammatory bowel disease (IBD) increases the risk of venous thromboembolism. Aim: To determine when patients are at high risk of thromboembolic events, including after major surgery, and to guide timing of thromboprophylaxis. Methods: Each inflammatory bowel disease patient from Clinical Practice Research Datalink, linked with Hospital Episode Statistics, was matched to up to five non-IBD patients in this cohort study. We examined their risk of thromboembolism in hospital and within six weeks after leaving hospital, with or without undergoing major surgery, and while ambulant. Hazard ratios were estimated using Cox regression, with adjustment for age, sex, body mass index, smoking and history of malignancy or thromboembolism. Results: Overall 23,046 inflammatory bowel disease patients had a thromboembolic risk 1.74 times (95% CI = 1.55–1.96) higher than 106,795 non-IBD patients. Among ambulant patients, the thromboembolic risk was raised during acute (hazard ratio = 3.94, 2.79–5.57) or chronic disease activity (3.97, 2.90–5.45) but their absolute risk remained below 5/1000 person-years. The hazard ratio for thromboembolism among in-patients not undergoing major surgery was 1.13 (0.63–2.02), compared to 2.43 (1.20–4.92) among surgical patients, with a near doubling of absolute risk associated with surgery (59.5/1000 person-years, compared with 31.1 without surgery). The absolute risk remained elevated within six weeks after leaving hospital (18.6/1000 person-years in inflammatory bowel disease patients after surgery). Conclusions: Inflammatory bowel disease patients are at an increased risk of venous thromboembolism. Absolute risks are raised during active disease, when in hospital, and after leaving hospital following major surgery.